2023
DOI: 10.1051/epjpv/2022033
|View full text |Cite
|
Sign up to set email alerts
|

Every cell needs a beautiful image: on-the-fly contacting measurements for high-throughput production

Abstract: The future of the energy transition will lead to a terrawatt-scale photovoltaic market, which can be served cost-effectively primarily by means of high-throughput production of solar cells. In addition to high-throughput production, characterization must be adapted to highest cycle times. Therefore, we present an innovative approach to detect image defects in solar cells using on-the-fly electroluminescence measurements. When a solar cell passes a standard current–voltage (I–V) unit, the cell is stopped, conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…[37] Relevant to this study, Kurumundayil et al have successfully used a GAN to improve the image quality of blurred EL images [38] and to remove unwanted marks when analyzing silicon wafer images. [39] This paper investigates the efficacy of using U-net, a deep learning model, to reduce noise in both EL and PL images. Previous research in other fields has demonstrated that U-nets outperform other models, including GANs, in terms of its architectural simplicity and effectiveness in denoising.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…[37] Relevant to this study, Kurumundayil et al have successfully used a GAN to improve the image quality of blurred EL images [38] and to remove unwanted marks when analyzing silicon wafer images. [39] This paper investigates the efficacy of using U-net, a deep learning model, to reduce noise in both EL and PL images. Previous research in other fields has demonstrated that U-nets outperform other models, including GANs, in terms of its architectural simplicity and effectiveness in denoising.…”
Section: Introductionmentioning
confidence: 95%
“…The models that have shown high performance in denoising applications [ 24 ] include autoencoders, [ 34 ] generative adversarial networks (GANs), [ 35 ] and U‐nets [ 36 ] with GANs and U‐nets performing particularly well. [ 37 ] Relevant to this study, Kurumundayil et al have successfully used a GAN to improve the image quality of blurred EL images [ 38 ] and to remove unwanted marks when analyzing silicon wafer images. [ 39 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation